An Evaluative Study On The Investment Behaviour Of Women Employees In Delhi NCR (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Working women want to be financially independent and secure. They want to invest their money and savings to handle critical situations at all stage of their lives. It is possible that the engagement of women in any society's financial affairs is one of the major important variables that contribute to the correct and sustainable growth of that society. Working women in the Delhi-National Capital Region are the focal point of this study, which investigates and analyses their investment behavior. This study is specified by its descriptive nature. All the information was acquired by the means of a structured questionnaire that included both closedand open-ended questions. A study strategy that was both quantitative and descriptive was utilized for the purpose of data collection. A total of 200 respondents were approached in order to obtain the information, and 113 of those respondents provided data that could be used and utilized. Additionally, descriptive and comparative analysis were conducted in order to analyze the data. According to the findings of the study, women remain firm and constant in their behavior of taking fewer risks, and they have a tendency to avoid making long-term investments. In addition to this, the study emphasizes on the fact that the major proportion of the female workers have a tendency to invest for higher returns. This study will, in the future, shed insight and light on the function that investment plays for working women as well as their attitudes towards various aspects related to investment.